Effect of endocyclophotocoagulation on refractive outcomes in angle‐closure eyes after phacoemulsification and posterior chamber intraocular lens implantation. Issue 1 (January 2016) - Wang, Jay Ching‐Chieh; Campos‐Möller, Xavier; Shah, Manjool; Sheybani, Arsham; Ahmed, Iqbal Ike K.
Abstract : Purpose : To compare postoperative refractive outcomes in angle‐closure eyes having phacoemulsification and intraocular lens (IOL) implantation with or without endocyclophotocoagulation (ECP). Setting : Single tertiary‐level ophthalmology practice. Design : Retrospective comparative study. Methods : Primary angle‐closure suspect (PACS), primary angle‐closure (PAC), or primary angle‐closure glaucoma (PACG) eyes that had phacoemulsification and IOL implantation with or without ECP from 2012 to 2014 were studied. Clinical data collected included axial length (AL), minimum and maximum keratometry (K) values, corneal powers, anterior chamber depth (ACD), corneal white‐to‐white (WTW), implanted IOL power, and postoperative manifest refraction. The Holladay 1 formula was used for IOL calculations. Primary and secondary outcome measures were the mean absolute error (MAE) and mean arithmetic error, respectively. Results : Sixty‐eight eyes with ECP and 71 eyes without ECP were included. There were no statistically significant differences between the 2 groups in age, sex, eye side, ethnicity, AL, minimum or maximum keratometry values, ACD, WTW, or implanted IOL power. The MAE was lower in the non‐ECP group (0.47 ± 0.32D versus 0.62 ± 0.43D; P = .0285). The mean arithmetic error showed a more myopic result in the ECP group (−0.54 ± 0.53D versus −0.26 ± 0.52D; P = .0017). Conclusion : In this study, patients with PACS, PAC, or PACG having phacoemulsification and IOL implantation with ECP had decreased predictability of the postoperative refraction and a small myopic shift compared with those without ECP. Financial Disclosure : Dr. Ahmed is a consultant to Alcon, Advanced Medical Optics, Bausch & Lomb, and Carl Zeiss. None of the other authors has a proprietary or financial interest in any material or method mentioned.